False‐negative HIV tests using oral fluid tests in children taking antiretroviral therapy from Harare, Zimbabwe. (29th August 2017) - Olaru, Ioana D.; McHugh, Grace; Dakshina, Suba; Majonga, Edith; Dauya, Ethel; Bandason, Tsitsi; Kranzer, Katharina; Mujuru, Hilda; Ferrand, Rashida A.
Abstract: Introduction : Rapid diagnostic tests (RDT) for HIV infection have high sensitivity and specificity, but in the setting of longstanding antiretroviral therapy (ART), can give false results that can lead to misinterpretation, confusion and inadequate management. The objective of this study was to evaluate the proportion of falsely negative results of a RDT performed on oral fluid in HIV‐infected children on longstanding ART. Methods : One hundred and twenty‐nine children with known HIV infection and receiving ART were recruited from the HIV Clinic at the Harare Central Hospital, Zimbabwe. HIV testing was performed on oral fluid and on finger‐stick blood. Results and Discussion : Children included in the study had a median age of 12 years (IQR 10–14) and 67 (51.9%) were female. Median age at HIV diagnosis was 5 years (IQR 3–6) and the median time on ART was 6.3 years (IQR 4.3–8.1). The oral fluid test was negative in 11 (8.5%) patients and indeterminate in 2 (1.6%). Finger‐stick blood test was negative in 1 patient. Patients with a negative oral fluid test had a higher CD4 cell count (967 vs. 723 cells/mm 3, p = 0.016) and a longer time on ART (8.5 vs. 6 years, p = 0.016). Conclusions : This study found that a substantial proportion of false‐negative HIV test results in children on longstanding ART when using an oral fluid test. This could lead to misinterpretation of HIV test results and in the false perception of cure or delayed diagnosis.